Ética dos nomes próprios: Análise pragmática das performances morais no uso cotidiano dos nomes próprios - Gurgel, Wildoberto Batista (2021)
The ethics of proper names as a philosophical inquiry into our moral performances in the everyday use of proper names. It presents the issue of the daily use of proper names in different scenarios and pronominal persons to conclude for the diversity of uses within a double game: language and power. Inscribing the name in the history, clearing one's name, not pronouncing some names and invoking others, or wanting to know the meaning of a name are just some of the performances related to the use of proper names. As a result, it aims to analyze the moral performances that are present in everyday life. It addresses this issue from the theoretical-methodological perspective of performative pragmatics, so that the relationship between the everyday use of proper names and the philosophical analysis of these uses looks at the performance of users who ascribe moral meaning to proper names. This meaning is plural and adjunct to the various uses, which is why the greatest interest falls on the nominative and interpellative uses to position the named entity in a certain social category: gender, class, ethnicity, creed, marital status, etc. The naming is understood as a double act (nominating someone to a position or giving a proper name to something or someone) and interpellation as a double movement (interpelling or responding to the question); both within a game of language and power. This shows that the use of proper names is: a) a common practice that ascribes moral meaning to proper names; b) an inseparable part of the collective ethos with which the use is involved; and, c) a way of living according to more or less established rules, in the game between inauthentic moral performances (subjugation) and authentic ones (empowerment). Based on this, it proposes that proper names are used to: a) inform about the named entities; (descriptive meaning); b) morally position the named entities based on the information provided (evaluative meaning); c) morally compel the entities named from the evaluative meaning assigned to them (prescriptive meaning); and, d) expressing emotions (emotional meaning). From this, it argues that the everyday use of proper names requires an ethics of proper names as the best possible explanation for what one does when using them.